Healthcare Diplomacy: Improving Cross-National Healthcare Delivery through International Community Engagement - Anjana Prusty (Edujavare Publishing, 2023)
Inequality of access and quality of health services across countries is an urgent global issue. Especially in developing countries, the challenge of providing quality health services is a serious problem. This article explains the role of “health diplomacy” through international service in improving the delivery of health services across borders through community engagement. The aim of this research is to explore how health diplomacy through the involvement of the international community can improve the delivery of health services across countries. We seek to identify effective strategies to facilitate international health cooperation and improve access and quality of health services in the countries involved. This research uses the Community Based Research (CBR) method with a mixed approach involving document analysis, case studies, and interviews with international health stakeholders. We analyze health diplomacy initiatives involving the international community in various country contexts and analyze their impact on the delivery of health services across countries. The research results show that health diplomacy through the involvement of the international community can play a key role in improving the delivery of health services across countries. Well-coordinated international collaboration can help countries share medical knowledge, resources, and technology. This has the potential to increase access to quality health care and reduce health inequalities between countries. Health diplomacy through international service and community engagement can be an effective tool in improving the delivery of health services across borders. This collaboration encourages joint efforts to address global health problems, opens the door to closer cooperation between countries, and has the potential to improve access and quality of health services throughout the world.